POTENSI PENYEDIAAN PAKAN HIJAUAN UNTUK TERNAK RUMINANSIA DI KECAMATAN BAJUIN KABUPATEN TANAH LAUT - Muhammad Salman; Anis Wahdi; Nursyam Andi Syarifuddin; Sista Rizqiana (JURNAL PENELITIAN PETERNAKAN LAHAN BASAH, 2024)
This research aims to determine the potential of regional forage for the development ofruminant livestock businesses in Bajuin District, Tanah Laut Regency. This research uses asurvey method. To measure the data research variables used, measurements were carried outusing the judgment sampling method. Judgment sampling is taking samples from relevant andavailable information from certain sources and seeking information from livestockstakeholders. Data were analyzed using a comparative method to determine the potential forproviding green fodder and developing beef cattle by comparing beef cattle populationsbetween villages in Bajuin District and also comparing it with existing literature studies. Theanalysis carried out in this research includes Basic Livestock Commodity Analysis,Contribution Analysis, Feed Potential Analysis, Regional Capacity Analysis, LivestockMaintenance Performance and SWOT Analysis. The results of the research show that from nine villages in Bajuin District, the average LQ was 0.94-1.03. In the contribution analysis, itwas found that nine villages had positive contribution analysis values with feed potential inBajuin District of 10,572.61 tonnes of DM/year which could accommodate 3,173.07 units oflivestock. This shows that the beef cattle population in Bajuin District has the potential fordevelopment. It can be seen from the available population and the abundant availability of feedso that the capacity of the area in Bajuin District, which consists of nine villages, can bedeveloped for the development of beef cattle farming. However, efforts are also needed fromseveral parties to maximize the potential they already have so that business development canbe carried out optimally.